The Effect of Modification of Zig-Zag Run Training on Dribbling Skills in Football Games - Junaedi, Dede; Rukmana, Anin; Sudrazat, Adang (Universitas PGRI Palembang, 2025)
This study aims to determine the effect of zig-zag run training modification on dribbling skills in soccer games for SSB KU-10 Porgap Pamoyanan Cicalengka participants. The research used is Quantitative with One Group Pretest-Posttest Design, the sample used is purposive sampling, data was collected using a dribbling test. The results of the data analysis showed the Normality Test Pretest value sig 0.088> 0.05 while the posttest value posttest value sig 0.762> 0.05, it can be concluded that the pretest-posttest data is normally distributed. The Homogeneity Test shows 0.594> 0.05, so the pretest and posttest data are homogeneous. Hypothesis testing using Paired Sample t-Test with sig value (2-tailed) shows the result of 0.000 <0.05 which means H1 is accepted and H0 is rejected, it can be concluded that there is an effect of zig-zag run training modification on dribbling skills (accepted). To find out how much the zig-zag run training modification affects dribbling skills, an R Square Test is carried out with a value of 0.923 which can be interpreted that the effect of the independent variable on the dependent variable is 0.923 x 100% = 92.3%. So with the modification of zig-zag run training in increasing dribbling skills significantly by 92.3%.